Role of Product Attributes in Apparel Buying Behaviour - Kulkarni, Preeti M.; Mahale, Prasad W. (International Journal of Psychosocial Rehabilitation, 2020)
In the apparel industry, there has been a huge demand for product variety. There are lots of product attributes in apparels to facilitate the product variety. This study explained the role of these factors in buying behaviour of the customers. It aimed to identify the prominent product attributes in apparel purchase. A convenient sample of 125 respondents within Nashik city was considered to collect data with the help of structured questionnaire and the data so collected was analyzed using SPSS. This study has special influence of COVID-19 outbreak. In such external environment, it was found that factors such as price, colour and comfort had a greater impact on people.